Reference Standards to Support Quality of Synthetic Peptide Therapeutics - Diane McCarthy; Ying Han; Kevin Carrick; Dale Schmidt; Wesley Workman; Paul Matejtschuk; Chinwe Duru; Fouad Atouf (Pharmaceutical Research, 2023)
Purpose Peptides are an important class of therapeutics. Their quality is evaluated using a series of analytical tests, many of which depend on well-characterized reference standards to determine identity, purity, and strength. Objective Discuss approaches to producing peptide reference standards, including vialing, lyophilization, analytical testing and stability studies. Methods Case studies are used to illustrate analytical approaches to characterize reference standards, including methods for value assignment, content uniformity, and identity testing. Methods described include NMR, mass spectrometry, and chromatography techniques for identity testing and HPLC and GC methods for assessing peptide content and impurities. Results This report describes the analytical strategy used to establish peptide reference standard and illustrates how results from multiple labs are integrated to assign a value to the final lyophilized vial. A two-step process for value assignment is described, which uses a mass balance approach to assign a quantitative value to a bulk peptide material. The bulk material is then used as a standard to assign a final value to the vialed material. Testing to confirm peptide identity and to ensure consistency of the vialed material is also described. Considerations for addressing variability, identifying outliers, and implementing stability studies are also presented. Conclusion The methods and case studies described provide a benchmark for best practices in establishing the preparation, analytical testing, handling, and storage of peptide reference standards for the pharmaceutical industry. Some peptide features, such as chiral or isobaric amino acids, may require additional techniques to ensure a full characterization of the peptide reference standard.

Understanding Quality Paradigm Shifts in the Evolving Pharmaceutical Landscape: Perspectives from the USP Quality Advisory Group - Jane Weitzel; Horacio Pappa; Gregory M. Banik; Amy R. Barker; Elizabeth Bladen; Narendra Chirmule; Joseph DeFeo; Jennifer Devine; Steven Emrick; Taha Kass Hout; Michael S. Levy; Gugu N. Mahlangu; et al. (The AAPS Journal, 2021)
Recent changes in the pharmaceutical industry have led to significant paradigm shifts in the pharmaceutical quality environment. Globalization of the pharmaceutical industry, increasingly rapid development of novel therapies, and adoption of new manufacturing techniques have presented numerous challenges for the established regulatory framework and quality environment and are impacting the approaches utilized to ensure the quality of pharmaceutical products. Regulators, industry, and standards-setting organizations have begun to recognize the need to rely more on integrated risk-based approaches and to create more nimble and flexible standards to complement these efforts. They also increasingly have recognized that quality needs to be built into systems and processes throughout the lifecycle of the product. Moreover, the recent COVID-19 crisis has emphasized the need to adopt practices that better promote global supply chain resilience. In this paper, the USP Quality Advisory Group explores the various paradigm shifts currently impacting pharmaceutical quality and the approaches that are being taken to adapt to this new environment. Broad adoption of the Analytical Procedure Lifecycle approach, improved data management, and utilization of digital technologies are identified as potential solutions that can help meet the challenges of these quality paradigm shifts. Further discussion and collaboration among stakeholders are needed to pursue these and other solutions that can ensure a continued focus on quality while facilitating pharmaceutical innovation and development.